PENGARUH OUTDOR LEARNING TERHADAP KEMAMPUAN MENULIS DESKRIPSI SISWA KELAS V SDN 53 SAULEYA KABUPATEN TAKALAR - Rayhan; Andi Adam; Anzar (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to determine the effect of using the outdoor learning method on the descriptive writing skills of fifth-grade students at SDN 53 Sauleya, Takalar Regency. This study used a quantitative approach with a pre-experimental method through a One Group Pretest–Posttest design. The subjects of this study were 37 fifth-grade students. The data collection technique used a descriptive writing ability test administered before and after the implementation of the outdoor learning method in the learning process. The results showed that students' descriptive writing skills improved after using the method. The average score of 59.59 in the pretest increased to 82.16 in the posttest. These results indicate that the use of the outdoor learning method significantly improved students' descriptive writing skills. The outdoor learning method helps students find ideas and express them in writing more easily through direct observation of real objects in their surroundings. Therefore, the outdoor learning method can be used as an alternative, effective learning method to improve the writing skills of elementary school students